The Analysis Study of Effect of Dietary Stearidonic Acid on Biomarkers of Lipid Metabolism: A Comprehensive Systematic Review - Raudha Kasmir; Putri Sakti Dwi Permanasari (International Medical Journal Corp. Ltd, 2024)
Introduction: The role of dietary oils rich in specific fatty acids, such as stearidonic acid (SDA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA), has been extensively studied for their effects on lipid metabolism and cardiovascular health. This study aims to evaluate the impact of these oils on lipid profiles, fatty acid composition, and metabolic outcomes in various populations. Methods: A systematic review was conducted by analyzing randomized controlled trials (RCTs), crossover studies, and experimental designs involving SDA, EPA, and DHA. Parameters assessed included changes in lipid profiles, EPA and DHA levels in erythrocytes, and other metabolic markers. Bias was evaluated across seven domains: temporal precedence, selection/allocation, confounding, administration of interventions, outcome assessment, participant retention, and statistical conclusion validity. Results: The studies demonstrated variable but significant increases in EPA levels across dietary oils, with SDA-rich oils showing moderate efficiency compared to EPA. DHA levels remained largely unaffected by SDA supplementation. Improvements in triglyceride levels and LDL cholesterol were observed, though some studies reported reductions in HDL cholesterol. Study quality was generally high, but some biases were noted in participant retention and detailed reporting of outcomes. Conclusion: Dietary oils rich in SDA and EPA effectively improve EPA status and influence lipid metabolism. However, their efficacy compared to direct EPA supplementation remains limited. Future studies should address biases and explore long-term clinical benefits.